Internet literacy as catalyst to digital literacy among users of Penang State Public Library / Raja Alwi Raja Omar - Raja Omar, Raja Alwi (2003)
Digital Literacy, one of 'functional literacy' aspect, is a relatively new concept that first emerged in the 1990's. The tremendous growths in the technological world where many things have been digitized need a new kind of literacy. Internet literacy and digital literacy are two distinctive things but digital literacy is best exemplified through Internet. The issue that wanted to be highlighted is whether Internet literacy or competency does make a person digitally literate. This study looks at the resemblance of an Internet literate user with digital literacy. As assumed by many studies, this studies revealed that those who are Internet literate does not necessarily become digitally literate when the main ingredient, critical thinking, is not applied in all area of Internet tools usage.